Study of the dose-volume parameters variation in tumor target volumes and organs at risk during nasopharyngeal carcinoma radiotherapy applying deformation registration - Yao, Xinsen; Gong, Guanzhong; Zuo, Guoping; Ren, Jianxin; Su, Ming; Yin, Yong (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
Background: During intensity-modulated radiotherapy (IMRT) for nasopharyngeal carcinoma (NPC), the volume of the target volume and the organs at risk (OARs) will change constantly, which may lead to differences between the actual dose received and the initial planned dose. In this study, the cumulative dose of the two plans was obtained by deformable registration. This study provides an approach to evaluate the dose volume of IMRT for the NPC objective. Methods: From July 2014 to May 2018, eighteen NPC patients who accepted simultaneous integrated boost IMRT were enrolled. All patients underwent simulation CT (CT1) and replanning CT (CT2) scans after 20–25 fractions of radiation therapy. The treatment plans were designed on CT1 and CT2 with the name of Plan1 and Plan2, respectively. The Planreg and Plandef were obtained after registering from CT2 to CT1 using rigidity and deformation technology by Velocity. Then the dose-volume indices of the tumor target volumes and OARs at Plan1, Plan2, Planrig and Plandef were compared. Results: The gross tumor volume (GTV) and the left and right parotid gland volumes decreased by 20.8% (P